Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction